The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
DOI: 10.14264/uql.2015.819
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic methane in Indonesian coal : assessing the potential using culture enrichment, molecular phylogenetic and isotopic analysis

Abstract: Biogenic coal bed methane (CBM) has gained considerable interest because of its potential to be regenerated. The research reported in this thesis evaluated the potential to develop Indonesian coals as CH 4 bioreactors using culture enrichment, molecular phylogenetic and isotopic composition analysis methods. The results increase the current understanding on microbial methanogenesis in coal, with a specific focus on Indonesian coals.Indonesian coals range in rank from lignite to bituminous, with anthracites occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
1
0
0
Order By: Relevance
“…Based on MG-Rast result, the genus found in coal waste dominated by Clostridium 51.28%, followed with Bacillus 35.29%, Pyramidobacter 6.13%, Desulfovibrio 2.04%, Planctomyces 1.38%, and Syntrophomonas 0.56% (Figure 1). This was consistent with (Susilawati 2015), who stated that bacterial species from the Clostridium genus were geopolymer hydrolyzers in biogenic Coal Bed Methane (CBM) reservoirs. This showed that after applying the treatment and growing bacteria in waste, it still showed biogenic coal.…”
Section: Lignite Coal Wastesupporting
confidence: 90%
“…Based on MG-Rast result, the genus found in coal waste dominated by Clostridium 51.28%, followed with Bacillus 35.29%, Pyramidobacter 6.13%, Desulfovibrio 2.04%, Planctomyces 1.38%, and Syntrophomonas 0.56% (Figure 1). This was consistent with (Susilawati 2015), who stated that bacterial species from the Clostridium genus were geopolymer hydrolyzers in biogenic Coal Bed Methane (CBM) reservoirs. This showed that after applying the treatment and growing bacteria in waste, it still showed biogenic coal.…”
Section: Lignite Coal Wastesupporting
confidence: 90%